2017
DOI: 10.1074/jbc.m117.805747
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-101 attenuates pulmonary fibrosis by inhibiting fibroblast proliferation and activation

Abstract: Aberrant proliferation and activation of lung fibroblasts contribute to the initiation and progression of idiopathic pulmonary fibrosis (IPF). However, the mechanisms responsible for the proliferation and activation of fibroblasts are not fully understood. The objective of this study was to investigate the role of miR-101 in the proliferation and activation of lung fibroblasts. miR-101 expression was determined in lung tissues from patients with IPF and mice with bleomycin-induced pulmonary fibrosis. The regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 42 publications
3
91
1
3
Order By: Relevance
“…Orotracheal administration of bleomycin following lenti-miR-9 treatment interrupted structural damage to the lungs, hence prevented pulmonary fibrosis in mice [69]. miR-101 decreased the mRNA and protein levels of TGFBR1, FZD4 and FZD6, and thus blocked NFATc2 and TGF-β1 signaling to attenuate fibroblast proliferation and activation [70].…”
Section: Pulmonary Fibrosismentioning
confidence: 98%
“…Orotracheal administration of bleomycin following lenti-miR-9 treatment interrupted structural damage to the lungs, hence prevented pulmonary fibrosis in mice [69]. miR-101 decreased the mRNA and protein levels of TGFBR1, FZD4 and FZD6, and thus blocked NFATc2 and TGF-β1 signaling to attenuate fibroblast proliferation and activation [70].…”
Section: Pulmonary Fibrosismentioning
confidence: 98%
“…We found that targets of specific miRNAs or RBPs are significantly enriched in translationally but not transcriptionally regulated genes, revealing their post-transcriptional regulatory footprint during cardiac fibroblast activation. miR-101 was previously reported to inhibit cardiac fibrosis via the TGFβ1 pathway 29 , block fibroblast activation 30 and is reduced in the lung and serum of IPF patients 31 . We show that TGFβ1 stimulation results in a loss of anti-fibrotic miRNA-101 in atrial fibroblasts, which is significantly associated with an increase in ribosome occupancy on a select number of target transcripts ( Supplementary File 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are short single-stranded RNA molecules of [19][20][21][22][23][24][25] nucleotides in length that mediate posttranscriptional gene silencing of target genes [5]. MiRNAs have been recognized as a distinct class of small regulatory RNAs in multiple species that regulate a wide variety of functions such as cell proliferation, differentiation, apoptosis, stress response, and immune response [6][7][8].…”
Section: Overview Of Mirnasmentioning
confidence: 99%
“…Profiling of miRNAs in the lung tissue from IPF patients was performed by different groups [18][19][20][21][22]. In IPF lungs, the expression of miR-21 and miR-155 was increased, whereas the expression of let-7a, miR-29, miR-30, and miR-101 was decreased [23][24][25]. MiR-21 expression was increased in the serum of IPF patients, and its levels correlated with a decrease in lung function [26].…”
Section: Ipf and Mirnasmentioning
confidence: 99%
See 1 more Smart Citation